Metallic one-dimensional heterostructure for gas molecule sensing - Prabal Dev Bhuyan (Nature Portfolio, 2021)
Abstract We have investigated a new metallic core–shell nanowire (NW) geometry of that could be obtained experimentally, that is silicon (Si) and germanium (Ge) NWs with cores constituted by group-10 elements palladium (Pd) and platinum (Pt). These NWs are optimized with two different diameters of 1.5 Å and 2.5 Å. The nanowires having diameter of 1.5 Å show semi-metallic nature with GGA-PBE calculation and metallic nature while spin orbit interaction (SOC) is included. The quantum conductance of the NWs increases with the diameter of the nanowire. We have investigated current–voltage (IV) characteristics for the considered NWs. It has been found that current values in accordance with applied voltage show strong dependence on the diameter of the NWs. The optical study of the NWs shows that absorption co-efficient peak moves to lower energies; due to quantum confinement effect. Furthermore, we have extensively studied optical response of Pd and Pt based core–shell NWs in O2 and CO2 environment. Our study on Si and Ge based metallic core/shell NW show a comprehensive picture as possible electron connector in future nano-electronic devices as well as nano gas detector for detecting O2 gas.